The effects of "grunting" on serve and forehand velocities in collegiate tennis players - O'Connell, D. G.; Hinman, M. R.; Hearne, K. F.; Michael, Z. S.; Nixon, S. L. (The Journal of Strength and Conditioning Research, 2014)
The aim of this study was to examine the effects of grunting on velocity and force production during dynamic and static tennis strokes in collegiate tennis players. Thirty-two (16 male and 16 female) division II and III collegiate tennis athletes with a mean age of 20.2 ± 1.89 years participated as subjects. Demographic and survey data were obtained before subjects completed a 10- to 15-minute warm-up of serves and ground strokes while grunting and not grunting. The subjects performed randomized sets (3 grunting and 3 nongrunting trials) of serves and forehand strokes both dynamically and isometrically. Stroke velocities and isometric forces were measured with a calibrated radar gun and calibrated dynamometer, respectively. Electromyographic (EMG) data from subjects' dominant pectoralis major and contralateral external oblique muscles were recorded and averaged for data analysis. A repeated measures multivariate analysis of variance (RM-MANOVA) compared dynamic stroke velocity, isometric muscle force, and peak EMG activity during each breathing condition at the 0.05 alpha level. The RM-MANOVA indicated that dynamic velocity and isometric force of both serves and forehand strokes were significantly greater when the subjects grunted (F = 46.572, p < 0.001, power = 1.00). Peak muscle activity in the external oblique and pectoralis major muscles was also greater when grunting during both types of strokes (F = 3.867, p = 0.05, power = 0.950). Grunt history, gender, perceived advantages, and disadvantages of grunting, years of experience, highest level of competition, and order of testing did not significantly alter any of these results. The velocity, force, and peak muscle activity during tennis serves and forehand strokes are significantly enhanced when athletes are allowed to grunt.